Grasslands and Shrublands of Kazakhstan and Middle Asia - Wagner, Viktoria; Bragina, Tatyana M.; Nowak, Arkadiusz; Smelansky, Ilya E.; Vanselow, Kim (Encyclopedia of the World's Biomes, 2020)
Kazakhstan and Middle Asia comprise 4 million km2 of plains, uplands and tall mountain ranges in the core of the Eurasian continent. The region's semi-arid climate, grazing pressure by wild and domestic ungulates, and long pastoral tradition, have given rise to a variety of open habitat types and a distinct flora and fauna. Grasslands and shrublands are a natural and dominant vegetation type in the forest-steppe and steppe zone of northern and central Kazakhstan, as part of the Eurasian grassland biome. In Middle Asia, grasslands and shrublands are widespread habitat types in the Tian Shan, Pamir-Alai and Pamir-mountain systems that have been recently acknowledged as a global biodiversity hotspot. Here, grasslands and shrublands are often semi-natural, formed by a long practice of logging, burning and domestic livestock grazing, and comprise a variety of vegetation types, including Eurosiberian meadows and steppe, Irano-Turanian semi-savanna and thermophilous shrublands. The most serious threats to grassland biodiversity and ecosystem functioning are habitat degradation, including conversion to cropland, pollution, urban development, under- and overgrazing, and illegal hunting. Notwithstanding these threats, Kazakhstan and Middle Asia still harbor vast areas of public, unfenced grasslands and shrublands that are traditionally managed and often embedded in regions with low human density. This makes the region a globally important area for biodiversity conservation.
Created from Fastlane, Scopus look-up